NATO Aggression Against Yugoslavia: International-Legal, Military Strategic and Geopolitical Consequences - E. G. Ponomareva; A. V. Frolov (Vestnik MGIMO-Universiteta, 2019)
On March 24, 1999, on the pretext of protecting human rights NATO began its aggression against a sovereign European state – the Federal Republic of Yugoslavia. Historically, it was the first military strike against a sovereign state in response not to external aggression, but to internal conflict. The escalation of the Kosovo conflict to the scale of a «humanitarian intervention» raised a sharp question about not only the contours and principles of the 21st century world system, but also about the limits of the functionality of supranational (first and foremost force) structures. The NATO aggression had both short-term and long-term consequences. The article analyzes three groups of consequences: international-legal, military strategic and geopolitical. In the analysis of international-legal consequences, we investigated the process of legitimation of «humanitarian intervention» and «responsibility to protect». In the analysis of military strategic consequences, the emphasis is given to the processes and procedures of the transformation of the Serbian army into a dysfunctional system and the creation of conditions for accession of the Republic to NATO. Since Serbia is the central element of the Balkan policy of Western countries and organizations, the question is extremely important. Geopolitical consequences of the aggression we analyzed through the prism of political technologies of political coups tested in Serbia in October 2000 and used later in different regions of the world. The study is preceded by a short historiographical review of the latest literature on the topic. The conducted multilevel analysis of the consequences of the NATO aggression in 1999 gives an opportunity to formulate fundamentally new conceptual foreign policy approaches of modern Russia foreign policy.